Key Players in Choline Metabolic Reprograming in Triple-Negative Breast Cancer - Iorio, Egidio; Caramujo, Maria José; Cecchetti, Serena; Spadaro, Francesca; Carpinelli, Giulia; Canese, Rossella; Podo, Franca (Frontiers in Oncology, 2016)
Triple negative breast cancer (TNBC), defined by lack of estrogen and progesterone receptors in the absence of protein overexpression/gene amplification of human epidermal growth factor receptor 2 (HER2), is still a clinical challenge despite progress in breast cancer (BC) care. 1H magnetic resonance spectroscopy (MRS) allows identification and non-invasive monitoring of TNBC metabolic aberrations and elucidation of some key mechanisms underlying tumor progression. Thus, it has the potential to improve in vivo diagnosis and follow-up, and identify new targets for treatment. Several studies have shown an altered phosphatidylcholine (PtdCho) metabolism in TNBCs, both in patients and in experimental models. Up-regulation of choline kinase-alpha, an enzyme of the Kennedy pathway that phosphorylates free choline (Cho) to phosphocholine (PCho), is a major contributor to the increased PCho content detected in TNBCs. Phospholipase-mediated PtdCho headgroup hydrolysis also contributes to the build-up of a PCho pool in TNBC cells. The oncogene-driven PtdCho cycle appears to be fine tuned in TNBC cells in at least three ways: by modulating the choline import, by regulating the activity or expression of specific metabolic enzymes, and by contributing to the rewiring of the entire metabolic network. Thus, only by thoroughly dissecting these mechanisms, it will be possible to effectively translate this basic knowledge into further development and implementation of Cho-based imaging techniques and novel classes of therapeutics.